Optimization of Ultrasonic Assisted Extraction of Carbamate Pesticide Residues from Purple yam by Response Surface Method - Wang, Z.F.; Shi, L.; Min, Y. (Asian Journal of Chemistry, 2014)
A novel and effective ultrasonic-assisted extraction technique is proposed for extracting carbamate pesticide residues from Purple yam. In the ultrasonic-assisted extraction technology, solvent types, solvent volume, ultrasound power, ultrasound extraction time and extraction times as significant factors were studied and optimized by response surface methodology over the extraction rate of the extracts, which the contents of extracts were determined by LC-MS. Response surface methodology analysis show good correspondence between experimental and predicted values. The adjusted coefficient of determination (Radj2) for the model was 94.33 %. Probability value (P < 0.001) demonstrates a very high significance for the regression model. The extraction efficiency of five carbamate pesticides of 101.25 % with ultrasonic-assisted extraction was obtained by dual extraction with solvent volume of 30 mL, ultrasonic power of 90 W and ultrasound extraction time of 15 min. The proposed ultrasonic-assisted extraction technique has demonstrated to be simple, practical and environmentally friendly for the sample preparation.